2020
DOI: 10.1021/acs.jpcb.0c01511
|View full text |Cite
|
Sign up to set email alerts
|

Near-Critical Phase Behavior in Polyelectrolyte Solutions: Effect of Charge Fluctuations

Abstract: The critical behaviors in polyelectrolyte (PE) solutions are studied by a renormalized Gaussian fluctuation theory. PEs are fully charged linear wormlike chains. The electrostatic interactions are considered in a continuum solvent while ignoring other interactions. The effects of temperature on the criticality are explored in a salt-free polyanion solution, and the effects of salt are explored in a symmetric mixed solution of polycation and polyanion. An unphysical phase coexistence (UPPC), in which a metastab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…[1] Such ionizable groups can dissociate in a polar solvent such as water, leaving charged groups on polymer chains and releasing Predicting the phase behavior of polyelectrolyte solutions with salt has been one of the challenging problems in polymer physics [30][31][32] and has been the subject of several recent studies. [33][34][35][36][37][38][39] Zhang et al [33] studied the phase behavior of fully-charged polyelectrolyte solutions both in salt-free condition and with added salt using a relatively simple liquid-state (LS) theory but demonstrated promising success in connection with experiments. Their approach is followed in this work but is extended to the more general case of weakly charged polyelectrolyte solutions by incorporating neutral segments to the theory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Such ionizable groups can dissociate in a polar solvent such as water, leaving charged groups on polymer chains and releasing Predicting the phase behavior of polyelectrolyte solutions with salt has been one of the challenging problems in polymer physics [30][31][32] and has been the subject of several recent studies. [33][34][35][36][37][38][39] Zhang et al [33] studied the phase behavior of fully-charged polyelectrolyte solutions both in salt-free condition and with added salt using a relatively simple liquid-state (LS) theory but demonstrated promising success in connection with experiments. Their approach is followed in this work but is extended to the more general case of weakly charged polyelectrolyte solutions by incorporating neutral segments to the theory.…”
Section: Introductionmentioning
confidence: 99%
“…Predicting the phase behavior of polyelectrolyte solutions with salt has been one of the challenging problems in polymer physics [ 30–32 ] and has been the subject of several recent studies. [ 33–39 ] Zhang et al. [ 33 ] studied the phase behavior of fully‐charged polyelectrolyte solutions both in salt‐free condition and with added salt using a relatively simple liquid‐state (LS) theory but demonstrated promising success in connection with experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Such an LS theory has also been applied to study the phase behaviors of concentration-asymmetric mixtures of polycation and polyanion solutions and has also revealed a wealth of interesting and complex phase separations scenarios [57]. Classical density functional theories (cDFT) for charged polymers have also been developed based on a similar framework and have found wide applications in many polyelectrolyte systems [58][59][60][61][62][63][64][65]. A complete theoretical understanding of the solution phase behaviors of charged polymers, however, remains challenging, not only because of the multi-component nature of the system (which, in the simplest case of a salt-free solution of fully charged polymers, consists of solvent, counterions, and charged polymers), but also because of the delicate interplay among various factors, including the translational entropy of each component, excluded volume interactions, chain connectivity, and more importantly the long-range electrostatic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In simple electrolyte solutions, the dispersion interactions (DPIs) between the ions and the solvent play a dominant role in determining the thermodynamic properties . The DPIs are particularly important for PEs because the charge fluctuation may be strong . In the salt-free case, molecular dynamics (MD) simulations showed that the DPI can greatly influence the nature of the association between PE chains .…”
Section: Introductionmentioning
confidence: 99%
“…11 The DPIs are particularly important for PEs 12 because the charge fluctuation may be strong. 13 In the salt-free case, molecular dynamics (MD) simulations showed that the DPI can greatly influence the nature of the association between PE chains. 12 If the solvent affinity is weak, the system is a homogeneous PE solution.…”
Section: Introductionmentioning
confidence: 99%